Carbon takeoff [carbon fiber composites]. - Guizzo, E.
This paper describes the novel design of Boeing's new 787 Dreamliner, which showcases a fuselage and wings made almost entirely of carbon-fiber composites. The composite wing is lighter and more resistant to fatigue and corrosion than aluminum wings, and will help save fuel and lower maintenance costs. More than just another all-new plane, the 787 represents an evolutionary transition for Boeing's commercial unit: from a traditional plane manufacturer to a global systems integrator. The company recruited contractors all over the world to help not only manufacture but also design the new plane. It's an ambitious project with a number of firsts in commercial aviation.
Keywords: Boeing 787 Dreamliner; Carbon-fiber composites; Commercial aviation; Commercial jet; Composite materials; Composite wings; Fatigue resistance; Fuselage